A Dependent Economy Model of Employment, Real Exchange Rate and Debt Dynamics: Towards an Understanding of Pandemic Crisis. Issue 1 (February 2022) - Basu, Moumita; Basu, Rilina; Nag, Ranjanendra Narayan
Given the unforeseen and uncertain circumstances during the pandemic, the role of government expenditure becomes extremely relevant in sustaining lives and livelihoods of the masses. This brings forth public sector deficit as a key issue of macroeconomic policy debate. This article aims at investigating the effects of an unanticipated adverse shock like COVID-19, on the real value of public debt, in a small open economy, consisting of traded and non-traded sectors, along with proposed management of such crisis with fiscal and monetary expansion. The results of policy-induced and exogenous shocks depend on the difference in the speeds of adjustments in real exchange rate, interest rate and real value of debt, and the associated multitudes of cross effects. While an unanticipated adverse shock like COVID-19 causes contraction of both traded and non-traded sectors and reduces consumption expenditure, investment expenditure and level of employment and real value of aggregate income in the short run, fiscal expansion causes higher real value of debt and lower real exchange rate. JEL Codes: E12, E62, H63